Odpowiedzi

2009-11-20T00:07:32+01:00
A) √12 = √4*3 = 2 √3
b) 2 √54 = 6 √6
c) 3,5 √50 = 3,5 √2*25 = 3,5 * 5 √2 = 17,5 √5
d) √25*2 + √2 = 5 √2 + √2 = 6 √2
e) √3*100 - 2 √3 = 10 √3 - 2 √3 = 8 √3
f) -2 √8*4 - 2 √8 = -2*2 √8 - 2 √8 = 4 √8 - 2 √8 = 2 √8
2 5 2
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-11-20T00:09:38+01:00
A) √2*√6 = √2*2*3 = 2√3
b) 2√3*√18 = 2√3*2*3*3 = 2*3√6 = 6√6
c) 7√10*½√5 = 7 * ½√2*5*5 = 3,5 * 5 √2 = 17,5√2
d)√50+√2 = √2*5*5*2 = 5 * 2 = 10
e) √300-2√3 = √2*2*5*5*3 - 2√3 = 10√3 - 2√3 = 8√3
f) -2√32-2√8 = -2√2*2*2*2*2 - 2√2*2*2 = -2*4√2 - 2*2√2 = -8√2 - 4√2 = -12√2
2 3 2
2009-11-20T00:22:34+01:00
A) √2*√6 = √2*√2*√3 = 2√3

b) 2√3*√18 = 2√3*√9*√2 = 2√3*3*√2 =6√6

c) 7√10*½√5 = 7√5*√2*½√5 = 7*5*½*√2 =35/2*√2

d)√50+√2 = √25*√2 +√2 = 5√2 +√2 = 6√2

e) √300-2√3 = √100*√3 - 2√3 =10√3 -2√3 = 8√3

f) -2√32-2√8 = -2√16*√2 - 2√4*√2 = -2*4√2 -2*2√2 = -8√2 -4√2 = -12√2